1855-1856 Tenn. Pub. Acts 34 - (:unkn) unknown (My University, 1855)
An Act to Amend and Reduce into One, the Acts Relating to the Charter of the Town of Clarkeville, ch. 32, § 2, pt. 20: To provide for the prevention and extinguishment of fires; to organize, establish and equip fire companies, hose companies, and hook and ladder companies; to regulate, restrain or prohibit the erection of wooden or combustible buildings in any part of the city; to regulate and to prevent the carrying on of manufactories dangerous in causing or producing fires; to regulate the storage of gun powder, tar, pitch, rosin, saltpetre [sic], gun cotton and all other combustible or explosive material[.]
Keywords: GUNPOWDER - STORAGE